Peers Affect Personality Development - Xiaoyue Shan; Ulf Zölitz (Institute of Labor Economics (IZA), 2022)
Do the people around us influence our personality? To answer this question, we conduct an experiment with 543 university students who we randomly assign to study groups. Our results show that students become more similar to their peers along several dimensions. Students with more competitive peers become more competitive, students with more open-minded peers become more open-minded, and students with more conscientious peers become more conscientious. We see no significant effects of peers'extraversion, agreeableness, or neuroticism. To explain these results, we propose a simple model of personality development under the influence of peers. Consistent with the model's prediction, personality spillovers are concentrated in traits predictive of performance. Students adopt personality traits that are productive in the university context from their peers. Our findings highlight that socialization with peers can influence personality development.
Keywords: I21; I24; J24; 330; personality; malleability; peer effects; experiment